Heritable human genome editing: our moral responsibilities towards future generations - Agius, Emmanuel (Medicina e Morale, 2021)
The uncharted territory of genome editing technology, which can be described as the Copernican revolution of our age, presents the challenge of the trade-offs between the benefits to people now and the known unknowns concerning future dangers and risks. It is for this reason that critics of human germline modification argue that it is unethical to harvest benefits in the immediate future while causing a whirlwind in the far-distant future! The current generation has, therefore, to make sensible decisions about the research and clinical application of human gene editing technologies to prevent far-reaching deleterious impact on an indefinite number of generations yet to come. Certainly, techniques of heritable human genome editing could increase vulnerability, discrimination and division among and between generations without the guidance of social justice which is inseparable from solidarity. Since the descendants of edited human embryos may be exposed to unknown, possibly negative long-term effects, without consenting to having these risks imposed on them, the thorny issues of harm, safety and precaution are crucial to address the knowledge-gaps and uncertainties implied the clinical application of human genome editing. Thus, the intergenerational moral consciousness and conscientiousness on the benefits and risks of human genome editing have to remain vigilant and alert!